Makna Denotasi, Konotasi, dan Mitos Nadhom Istigosah KH Khoer Affandy: Kajian Semiotika Roland Barthes - Wihandani; Retty Isnendes (Institut Agama Islam Negeri Metro, 2026)
This study aimed to analyze the denotative, connotative, and mythical meanings in the Sundanese Nadhom Istigosah by KH. Khoer Affandi uses Roland Barthes's theory of semiotics. The method used was qualitative descriptive, analyzing 18 stanzas of the nadhom grouped into five thematic categories: creed, Sufism, society and leadership, the afterlife, and prayer and supplication. The results showed that at the denotative level, the nadhom functioned as a structured guide for collective prayer. At the connotative level, the text contained cultural values of the Sundanese pesantren such as asceticism, love for the Prophet, and rejection of injustice. At the mythical level, the nadhom constructed four belief systems: the power of collective prayer, blessings through a spiritual chain, justice based on Islamic law, and the afterlife as the true goal. This study concluded that the Sundanese Nadhom Istigosah is not merely a prayer text but a layered semiotic system that effectively transmitted Islamic values and Sundanese local wisdom across generations.